2012
DOI: 10.1016/j.virol.2011.11.015
|View full text |Cite
|
Sign up to set email alerts
|

NRIP enhances HPV gene expression via interaction with either GR or E2

Abstract: We previously identified a gene, nuclear receptor-interaction protein (NRIP), which functions as a transcription cofactor in glucocorticoid receptor (GR) and human papillomavirus E2 (HPV E2)-driven gene expression. Here, we comprehensively evaluated the role of NRIP in HPV-16 gene expression. NRIP acts as a transcription cofactor to enhance GR-regulated HPV-16 gene expression in the presence of hormone. NRIP also can form complex with E2 that caused NRIP-induced HPV gene expression via E2-binding sites in a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…COS-7 is a monkey kidney fibroblast-like cell line purchased from American Type Culture Collection (ATCC; Manassas, VA, USA). HEK293 and C33A are human embryonic kidney and cervix carcinoma cell lines, respectively [15] , [29] . All the cells were maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% FBS, 1% MEM nonessential amino acids solution (Invitrogen), 2 mM L-glutamine, and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…COS-7 is a monkey kidney fibroblast-like cell line purchased from American Type Culture Collection (ATCC; Manassas, VA, USA). HEK293 and C33A are human embryonic kidney and cervix carcinoma cell lines, respectively [15] , [29] . All the cells were maintained in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% FBS, 1% MEM nonessential amino acids solution (Invitrogen), 2 mM L-glutamine, and antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…Diante do uso do anticoncepcional e em se tratando da condição de união estável que grande parte das jovens 46,8% já vivencia, prevalece a preocupação diante de uma gravidez indesejada e não mais com a possibilidade de contrair uma infecção sexualmente transmissível. Vale ressaltar aqui que o uso prolongado do contraceptivo oral aumenta o risco de desenvolver carcinoma cervical em mulheres com HPV, por conterem hormônios como dexametazona, progesterona e estrógenos que intensificam a expressão genética do HPV 29 .…”
Section: Discussionunclassified
“…Many studies have previously reported the ability of the HPV-16 E6/E7 oncoproteins to disrupt the normal process of differentiation of human foreskin keratinocytes [21] by targeting key tumour suppressors, such as p53 [22] and pRb [23], resulting in increased levels of cell survival proteins, such as Akt [24], and disruption of the cell cycle [25]. The HPV E2 protein functions as a repressor or an activator of early gene transcription, which regulates viral transcription and genome replication [26]. Disruption of the viral E2-gene, which controls the transcription of oncogenes E6 and E7 that manipulate the cell cycle and the ability of apoptosis, has been associated with poor outcomes.…”
Section: Discussionmentioning
confidence: 99%